Legal Analysis of Decision No. 575/Pdt/2019/Pt.Bdg Regarding Sales and Purchase Agreements Containing Elements of Fraud through the Principle of Consensuality - Hafizh, Fauzan; Lubis, Syofiati (LEGAL BRIEF, 2025)
This study discusses the application of the principle of consensualism in contract law, particularly in the case of a sale and purchase agreement containing elements of fraud as reflected in the Bandung High Court Decision Number 575/PDT/2019/PT.Bdg. The main focus of the study is to examine the validity of the sale and purchase agreement if there is a defect in will arising from fraud (bedrog) and its legal implications for the parties. The research method used is normative juridical with a library approach, which emphasizes the analysis of articles of the Civil Code, legal literature, and related court decisions. The results of the study indicate that the principle of consensualism as a requirement for the validity of an agreement (Article 1320 of the Civil Code) is not sufficient to be interpreted only with formal agreement, but must be based on free will, honesty, and without fraud. In this case, the binding agreement for the sale and purchase of a house (SP3R) was declared legally invalid because the object of the agreement did not match what was promised, so that the agreement of the parties was not born purely. The panel of judges emphasized that agreements arising from fraud can be annulled and even declared null and void (Article 1321 of the Civil Code), and all legal consequences must be restored, including the return of payment to the buyer. Thus, this study confirms that the principle of consensualism in Indonesian contract law cannot be separated from the principles of honesty, propriety, and good faith. This decision also strengthens the doctrine that agreements containing elements of fraud lose their legal legitimacy and do not produce legal consequences binding on the parties